THE USE OF SUBSTANDARD VOCABULARY AS TRANSGRESSIVE COMMUNICATIVE STRATEGY IN THE FIELD OF MODERN MASS MEDIA - Y. Perepelitsyna; I. Kupreeva (Гуманитарные и юридические исследования)
The focus of this work is on comprehension of active process in the modern Russian language: changes in lexis and grammar, widening of stylistic variability and social functioning of the language, formation of a particular communicative area, which has a virtual status, and new strategies of speech behavior. In this article the original concept of language transgression is provided, which is deined by cultural ground of post-industrial social formation, postmodern philosophy as well as postnonclassical scientiic paradigm, inherent laws of language development and creative power of the language. This work deals with the genesis of philosopheme of transgression, the origin of which is traced in Fichte, Kant and Heidegger works. The final articulation was acquired in the scientiic works of French postmodern philosophers such as Foucault, Blanchot and Bataille. In addition, Russian philologist Lotman has made a significant contribution in analysis of transgressive phenomenon. In wide cross-cultural aspect, the transgression is considered as universal and flexible strategy of transcending social, moral and religious standards, language restrictions and structures. The embodiment of transgression of language area is understood as destruction and reduction of the codiied system of written form of the language. The penetration of substandard highly specialized vocabulary in communicative ield of mass media is regarded as one of the variants of this process. On the one hand, it serves practical aims of conscious communicative strategy, that is reaching an absolute interest, a full trust and a perception of the recipient, destruction of personal boundaries of communicators (blending of friend-or-foe words through the infusion of spoken elementin substantive indirect forms of writing or TV or radio communication). On the other hand, such speech behavior is dictated by determined demand of modern person in breaking rules and prohibitions, which is used as epistemological framework. In this research, the cross-curricular links of modern humanitarian knowledge are actualized.